MONITORING OF DANCE PROGRAM EFFECTS, AS THE CHOSEN SPORTS ACTIVITY IN THE PSYSICAL EDUCATION COURSE, FOCUSED ON MOTOR SKILS TRANSFORMATION OF NINETH GRADE PUPILS - Branislav Radulović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The dance is realized as an elective subject within the obligatory elective program in physical education teaching in Montenegro with weekly fund of two classes. On the sample of 112 examinees of both sexes there has been applied a battery of eight motor tests aimed to determine the effects of elective teaching on the transformation of motor skills of the pupils. Quarterly experimental treatment did not contribute to the improvement of the motor skills of the examinees, considering the fact that between the experimental and control group statistically significant differences haven't been determined. The negative trend in the number of pupils in recent years who chose dance within the elective teaching of physical education in Montenegro implies the fact that pupils aren't satisfied with the implementation of the offered content. That is why it is primarily necessary to further educate the professors of physical education who will be able to adjust the dance content to the age, sex and interests of the pupils.